Illimani 2015 firn-core (Bolivia, 6300 m) black carbon record between 1995 to 2015 CE - Michael Sigl (PANGAEA, 2024)
The glacier on Nevado Illimani in the eastern Bolivian Altiplano is one of the few in the mid- to low-latitudes giving access to ice covering the entire Holocene. The impurity and stable isotope in water records extracted from the Illimani ice core contain information on the composition of the past atmosphere and climate conditions over time. Here we provide a continuous high-resolution (median 3 cm water equivalent per sample) record of concentrations of refractory black carbon (rBC) from a 25.7 m long firn core drilled in 2015 named Illimani 2015 (Bolivia, 6300 m asl., 16°38 extquotesingle58.57 S, 67°47 extquotesingle03.57 W) encompassing the period 1995 to 2015 CE. At the Paul Scherrer Institute rBC was analyzed with a Single Particle Soot Photometer (SP2, Droplet Measurement Technologies) and a jet (APEX-Q, Elemental Scientific Inc.) nebulizer to aerosolize the aqueous samples (Osmont et al., 2019). Firn-core dating is based on annual-layer counting and the firn core overlaps with the 139 m deep Illimani99 ice core. This dataset underpins analyses of anthropogenic and natural emissions of aerosol species in South America (Osmont et al., 2019).